Studi kualitatif tentang penggunaan media gambar interaktif dalam meningkatkan pemahaman geometri dasar pada siswa kelas 4 SDN 2 Begawat - Ananda, Candra; Loustiawaty, Lousy (Papanda Publisher, 2025)
Geometry is often considered abstract and difficult for elementary students because of limited use of concrete and engaging media. This issue often reduces motivation and weakens understanding of basic geometry concepts. This study aims to determine the effectiveness of interactive image media in teaching geometry to fourth-grade students at SDN 2 Bagawat, Kecamatan Selajambe, Kabupaten Kuningan. The research employed a descriptive qualitative approach with a case study method. Data were obtained through observation, interviews, and documentation, then analyzed thematically using data reduction, data presentation, and conclusion drawing. The findings indicate that interactive image media increased student participation, clarified abstract concepts such as shapes and angles, and created a more engaging and enjoyable learning atmosphere. Teachers also reported that the media made it easier to deliver materials and stimulated student responsiveness. This research shows that interactive image media has a significant impact on mathematics learning in elementary schools. By turning abstract geometry into concrete experiences, it improves comprehension, fosters motivation, and supports the development of critical and creative thinking. Thus, this strategy can be an innovative alternative for mathematics instruction at the primary level